(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Forensic medicine plays a crucial role in the intersection of healthcare and the legal system, serving as a pivotal component in the administration of justice. In Saudi Arabia, the teaching of forensic medicine faces a myriad of challenges, from structural limitations within educational institutions to the pressing need for enhanced interdisciplinary collaboration among forensic professionals. [...]